P87 The use of a virtual clinic to speed up and improve the cancer diagnostic pathway – 2 year experience. (15th November 2016) - McIver, A; Maddock, N; Dunbar, J; Hughes, J; Ledson, MJ; Smyth, C; Walshaw, MJ
Abstract : In order to speed up the diagnostic pathway, in January 2014 we set up a "straight to CT" service for patients with suspected lung cancer from primary care, where positive scans undergo immediate chest physician review to decide the next diagnostic test and a lung cancer nurse specialist (CNS) offers the patient a telephone assessment to plan this. We have looked at the utility of this "virtual clinic" in the management of our patients with lung cancer over the first 2 years, in particular paying attention to patient uptake and satisfaction, and outcomes. Of about 300 patients annually who have been triaged in this way, 82% have chosen the virtual clinic, 13% preferred or the CNS advised a outpatient appointment, 4% required immediate inpatient referral, and the remaining and 1% were referred back to the GP as outpatient intervention not felt appropriate (too unwell). Overall, 75% subsequently were diagnosed with lung cancer. For those patients who chose the virtual clinic consultation, feedback has been overwhelmingly positive. This has been captured qualitatively at the time and at subsequent events e.g. patients report feeling well informed and supported, and quantitatively by an ongoing survey: 98% prefer the telephone clinic versus clinic appointment, 97% felt prepared for next test. This study has shown that performing a number of diagnostic investigations using a telephone support is not only feasible but preferred by patients with suspected lung cancer. By avoiding unnecessary clinic attendances it improves patient convenience, speeds up the diagnostic pathway and reduces unnecessary costs. This early CNS assessment and interventions reduces the level/scope of patient concerns prior to the time of diagnosis, this has further significance to the team formalising the Holistic Needs Assessment process. CNSs are best placed to do the consultations as they have the specialist skills and knowledge of the local clinical pathways, tests, disease symptomology and ultimately provide the continuity throughout the diagnostic pathway through to treatment and we recommend this to other cancer units.